The Marketing Strategy for Convection Production Results in Samong Village, Ulujami District, Pemalang - Pujianto, Eko; Adinugraha, Hendri Hermawan (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
The digital era encourages convection entrepreneurs in Samong village to try new ways to market their products. With the emergence of marketplaces, goods-to-goods services that can reach almost all parts of Indonesia that provide convenience in marketing their products. The research aims to find out how to maintain and develop a convection business, how to market convection products in Samong village and how to influence the progress of the digital era on the marketing of convection products in Samong village. The research method used in this research is qualitative descriptive analysis method. The results obtained from this study, namely things that can be done to maintain the convection business are to improve and maintain product quality, harmonious relationships with employees, harmonious relationships with co-workers (distributors/clothing traders) and also use marketing strategies appropriate and effective. Meanwhile, to develop its convection business, namely by making new innovations in accordance with fashion trends, expanding the market as wide as possible and using digital media as a medium for marketing its products. The marketing strategy carried out by several resource persons is by collaborating with distributors and clothing traders, as well as expanding the market, as well as with digital media. As for the influence of the progress of the digital era on the marketing of convection production, which was previously dominant by traveling around the market offering products, Cooperation with distributors and clothing traders began to switch to using digital media for marketing media.